2014
DOI: 10.1097/qai.0000000000000106
|View full text |Cite
|
Sign up to set email alerts
|

Medical Injection Use Among Adults and Adolescents Aged 15 to 64 Years in Kenya

Abstract: Background Unsafe medical injections remain a potential route of HIV transmission in Kenya. We used data from a national survey in Kenya to study the magnitude of medical injection use, medication preference, and disposal of medical waste in the community. Methods The Kenya AIDS Indicator Survey 2012 was a nationally representative population-based survey. Among participants aged 15–64 years, data were collected regarding medical injections received in the year preceding the interview; blood samples were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
1
4
1
1
Order By: Relevance
“…Young children may get pricked from used needles discarded around the household or within the community although our survey showed that the proportion of households affected was small (<5%). The low rate of reported harm associated with SMW is consistent with earlier studies in Kenya [ 34 ] and USA [ 35 ]. Furthermore, the use of non-rigid containers (cellophane bags) for temporary storage of household solid waste containing SMW by some households is a potential source of exposure.…”
Section: Discussionsupporting
confidence: 89%
“…Young children may get pricked from used needles discarded around the household or within the community although our survey showed that the proportion of households affected was small (<5%). The low rate of reported harm associated with SMW is consistent with earlier studies in Kenya [ 34 ] and USA [ 35 ]. Furthermore, the use of non-rigid containers (cellophane bags) for temporary storage of household solid waste containing SMW by some households is a potential source of exposure.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, injections were often described as less favoured due to pain and infection-related side effects. While these findings are in contrast to several previous studies highlighting a strong patient preference for injections in the developing world, [36][37][38] studies conducted in Ethiopia have found injections to be the preferred administration format in only 15-42% of studied populations. [39][40][41] Ease of product use and heat-stability were the most significant anticipated advantages of an oxytocin inhaler cited by all stakeholders, who largely expressed a willingness to Perceived acceptability of an inhaled oxytocin for the prevention of postpartum haemorrhage in Ethiopia Journal of Global Health Reports accept and use this type of product as long it had equivalent efficacy to the injection.…”
Section: Discussioncontrasting
confidence: 99%
“…FGD results were consistent with our expectations that injections would be generally viewed more favorably in Kenya than in the U.S., and with research from the 2012 Kenya AIDS Indicator Survey. 16 Of the 13,673 survey participants who answered questions about medical injections, 36% reported receiving one or more injection in the past 12 months and 51% preferred receiving an injection over a pill. Surprisingly, survey responses indicated 47% of participants strongly or somewhat agreed that they “hate getting injections and try to avoid whenever possible.” It is possible the burden of daily dosing was so heavy that some were inclined toward an injectiable ART option even given dislike of needles.…”
Section: Discussionmentioning
confidence: 99%